Alternate Facts and Reality Effects in Antoine Bello’s Roman américain - Jennifer Willging (Studies in 20th & 21st Century Literature, 2018)
Like several of Antoine Bello’s eight other novels to date, Roman américain contains a staggering array of minute details, which includes the names of dozens of fictional characters, businesses, associations, institutions, locations, and publications. These fictional proper nouns are intertwined throughout the novel with dozens of real ones, and this promiscuous intermixing contributes to the careful construction of a fictional world that rivals the real one in all its complexity. In this essay I examine Bello’s masterful production in Roman américain of verisimilitude, which he creates largely but not exclusively though his exploitation of the documentary fiction genre. I then link the author’s predilection for realist literary devices to his preoccupation with an ontological, epistemological, and ethical problem that would appear, given the recent coinage of the dubious expression “alternate facts,” to be growing ever larger and more menacing in our digital era: the regular production by the media and any number of other “reliable” entities of new “truths.” Bello constructs in Roman américain a hyper-realist world, but then, I argue, systematically deconstructs it by revealing to his readers, little by little, its fictionality. He does so not in the interest of postmodern play, but rather to entreat his readers to sharpen the critical reading skill they so desperately need to find their way through the moral morass that is the “information age.”
Keywords: Antoine Bello; Roman américain; verisimilitude; reality effect; documentary fiction; French; literature; 21st century